2004
DOI: 10.1128/mcb.24.1.96-104.2004
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role for ADAM19 in Cardiovascular Morphogenesis

Abstract: Congenital heart disease is the most common form of human birth defects, yet much remains to be learned about its underlying causes. Here we report that mice lacking functional ADAM19 (mnemonic for a disintegrin and metalloprotease 19) exhibit severe defects in cardiac morphogenesis, including a ventricular septal defect (VSD), abnormal formation of the aortic and pulmonic valves, leading to valvular stenosis, and abnormalities of the cardiac vasculature. During mouse development, ADAM19 is highly expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 53 publications
3
102
1
Order By: Relevance
“…5B). In addition, we found that the expression levels of several genes associated with embryonic development, including Adam19, Chd8, Git1, Lims1/Pinch1, Pogz and Sulf1, were increased in Dnmt3l-KO MEFs (Nishiyama et al 2004, Zhou et al 2004, Liang et al 2005, Holst et al 2007, Pang et al 2009). We further investigated the DNA methylation state of CpG islands in the promoter regions of three differentially expressed genes Adam19, Git1 and Lims1.…”
Section: Dnmt3l-ko Mef Cellsmentioning
confidence: 82%
“…5B). In addition, we found that the expression levels of several genes associated with embryonic development, including Adam19, Chd8, Git1, Lims1/Pinch1, Pogz and Sulf1, were increased in Dnmt3l-KO MEFs (Nishiyama et al 2004, Zhou et al 2004, Liang et al 2005, Holst et al 2007, Pang et al 2009). We further investigated the DNA methylation state of CpG islands in the promoter regions of three differentially expressed genes Adam19, Git1 and Lims1.…”
Section: Dnmt3l-ko Mef Cellsmentioning
confidence: 82%
“…Experiments in ADAM19 knockout mice showed that ADAM19 is possibly involved in the vascular ensheathment of smooth muscle cells (20 (3,26). The RGD containing disintegrin functions as an adhesion molecule that mediates cellcell interaction via alphavb3 (27).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in monocytes suggest that ADAM19 is important for early adhesion and migration from the blood into peripheral tissue (8). Furthermore, genetic inactivation of ADAM19 in mice resulted in perinatal death due to severe cardiac dysfunction (20,21).…”
Section: + T Cells (T Helper Cells) and Cd8mentioning
confidence: 99%
“…ADAMs are currently emerging as the major mediators of ectodomain shedding (for example [80,124]). Besides their relevance to inflammatory diseases and cancer, ADAMs are putative key regulators of morphogenesis (for example, [3,70,178]). …”
Section: Cell Adhesionmentioning
confidence: 99%